Teacher-Student Interaction and Students' Motivation as Predictors of Students' Mathematics Achievement - Brent Diesel Jake Delos Santos; Samantha Maricon Badayos; Jonalyn Beller; Priscilla Mae Ponce; Leslie Cagas; Abdul Jamara (Journal of Social, Humanity, and Education, 2026)
Purpose: This study aimed to determine whether teacher-student interaction and students' motivation are significant predictors of students' mathematics achievement. Research Methodology: A quantitative descriptive correlational approach was used, with stratified random sampling to select 120 first- and second-year BSED-Mathematics students from Davao del Norte State College. Three sets of validated questionnaires were used to measure the variables. Statistical analyses included mean, standard deviation, Pearson’s r, and multiple linear regression. Results: Significant positive relationships were found between teacher-student interaction (r = 0.716, p < 0.01) and students’ motivation (r = 0.714, p < 0.01) and mathematics achievement. Both teacher-student interaction (? = 0.417) and students' motivation (? = 0.412) were significant predictors of mathematics achievement. The adjusted R-squared value of 0.585 indicates that 58.5% of the variation in mathematics achievement was explained by the model. Conclusions: Teacher-student interaction and student motivation are significant predictors of mathematics achievement among first- and second-year BSED-Mathematics students. Limitations: The study sample was limited to 120 students from a single institution, which limited generalizability. The researcher-made 50-item test for "mathematics achievement" had limitations, particularly after the post-hoc analysis removed 23 items. Contributions: This study emphasizes the importance of teacher-student interaction and student motivation as key factors influencing mathematics achievement.